2021
DOI: 10.1080/14658011.2021.2008714
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lignin as potential green filler in an optimally designed solution grade styrene–butadiene rubber (SSBR) based tyre tread compound

Abstract: In this study, solution grade styrene-butadiene rubber (SSBR) compound was prepared by partial replacement of silica with lignin. The compounds were designed and optimised using an L9 orthogonal array (using Taguchi method) targeting 'magic triangle'. Cure rate index (CRI), reinforcement index (RI) and hysteresis loss (loss tangent at 60°C) were considered as the responses. Thermo-gravimetric analysis and Differential scanning calorimeter is used to assess thermal degradation and intramolecular reactivity of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Strong intra‐molecular hydrogen bonds formed within lignin makes it difficult to disperse in rubber matrix. [ 9 ] Thus, in presence of silane coupling agent, it acts as a bridge between non‐polar rubber and polar lignin forms interaction. However, at similar lignin level, ENR acts as a compatibilizer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong intra‐molecular hydrogen bonds formed within lignin makes it difficult to disperse in rubber matrix. [ 9 ] Thus, in presence of silane coupling agent, it acts as a bridge between non‐polar rubber and polar lignin forms interaction. However, at similar lignin level, ENR acts as a compatibilizer.…”
Section: Resultsmentioning
confidence: 99%
“…But abundance, biodegradability, and cost‐effectiveness of lignin still create enthusiasm in researchers to use this as green, sustainable filler. [ 9 ] It is the second most abundant naturally occurring material after cellulose. [ 10 ] Lignin is having heterogeneous, branched, three‐dimensional structure.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to silica, lignin was also investigated as the second filler to balance the "magic triangle". 97 Yu et al 98 found that NR composites with 30 phr lignin had little influence on the rolling resistance, but improved the wet gripping performance than the control sample with the same amount of silica (Figure 7c). Jiang et al 42 prepared a variety of chemically modified lignin with formaldehyde (LF), glyoxal (LG), glutaraldehyde (LGD), and propylene oxide (HL), respectively, and found that the aggregation structure of the modified lignin strongly depends on their molecular structure.…”
Section: Dynamic Performancementioning
confidence: 97%
“…In tire application, silica is intensively consumed ranking after CB, and generally as the second filler to interrupt the filler–filler network formed by CB and weaken the hysteresis loss mainly caused by the dynamic movement of the filler–filler network. Similar to silica, lignin was also investigated as the second filler to balance the “magic triangle” . Yu et al found that NR composites with 30 phr lignin had little influence on the rolling resistance, but improved the wet gripping performance than the control sample with the same amount of silica (Figure c).…”
Section: Performance Of Rubber/lignin Compositesmentioning
confidence: 99%
“…Those properties make lignins suitable for a wide sphere of applications, such as adhesives, flocculants, surfactants, dispersant agents, compatibilizers, stabilizers, flame retardants, binders, additives to composites, in energy storage, and 3D printing applications [ 8 , 20 , 21 , 22 , 23 , 24 , 25 ]. Their high amount of carbon, mechanical stability, and good rheological and viscoelastic properties also make them suitable candidates as additives and fillers for rubber compounds [ 1 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The biggest problem arising from the application of lignins in rubber formulations is the deterioration of the physical–mechanical properties of the final products, mostly due to the poor homogeneity and compatibility between the rubber and the filler in the rubber–filler interface.…”
Section: Introductionmentioning
confidence: 99%